Mean platelet volume in a patient with male hypogonadotropic hypogonadism: the relationship between low testosterone, metabolic syndrome, impaired fasting glucose and cardiovascular risk. Issue 7 (October 2015) - Carlioglu, Ayse; Durmaz, Senay Arikan; Kibar, Yunus Ilyas; Ozturk, Yasin; Tay, Ahmet
Abstract : Isolated male hypogonadotropic hypogonadism (IHH) can be congenital or acquired. Mean platelet volume (MPV), determinant of platelet function, is an independent risk factor for cardiovascular disease (CVD). The aim of this study was to evaluate MPV values in male IHH and the relationships between MPV, low testosterone levels, metabolic syndrome, impaired fasting glucose (IFG) and cardiovascular risk. Thirty-one patients with untreated, normosmic, isolated, male IHH (mean age 22.5 ± 7.58 years) and 30 age and BMI-matched healthy individuals (mean 22.51 ± 4.94 years) were included in the study. All hormonal analyses were done by chemiluminesance assay. All study participants were evaluated by biochemical and platelet parameters. MPV were significantly higher in IHH than controls (8.6 ± 0.65 and 7.6 ± 0.54 fl, respectively; P  = 0.000). MPV had a positive correlation between metabolic syndrome ( r  = 0.444; P  = 0000), IFG ( r  = 0.371; P  = 0.04), insulin ( r  = 0.820; P  = 0.02), homeostasis model assessment (HOMA)-IR ( r  = 0.822; P  = 0.0023) and BMI ( r  = 0.373; P  = 0.012). MPV had a negative correlation between total testosterone ( r  = −0.586; P  = 0.0000), free testosterone ( r  = −0.634; P  = 0.0000), luteinizing hormone ( r  = −0.471; P  = 0.0000) and FSH ( r  = −0.434; P  = 0.0000). Although control patients did not have metabolic syndrome and IFG, IHH patients had metabolic syndrome and IFG significantly more often ( P  < 0.001, P  = 0.003, respectively). Age, metabolic syndrome, IFG, BMI, fasting glucose, insulin, CRP and HOMA-IR were independent predictive factors of MPV in the multiple regression analysis. These results suggest that men with IHH are susceptible to increased platelet activation and increased MPV values that contribute to an increased risk of cardiovascular complications. From this study, it has been observed that IHH with low testosterone may be a feature of the metabolic syndrome, IFG, increased MPV levels and cardiovascular risk in young adult males.